Las instrucciones de los diputados orientales a la Asamblea del Año XIII - Frega Novales, Ana (2013)
El artículo analiza las instrucciones dadas a los diputados de la naciente Provincia Oriental en 1813 como expresión del ejercicio de la "soberanía particular de los pueblos" proclamada por el artiguismo. A través del cotejo del articulado de las distintas versiones procura una aproximación a la recepción, apropiación y reelaboración local de las ideas acerca de la construcción de un nuevo orden político en el Río de la Plata
The article analyzes the instructions given to the deputies of the emerging Oriental Province in 1813 as an expression of the exercise of "individual sovereignty of the people" proclaimed by Artiguism. Through the comparison of the different versions, this work seeks an approach towards the local reception, appropriation and reworking of the ideas regarding the construction of a new political order in the River Plate
Keywords: Soberanía popular; Representación; José Artigas; Sovereignty of the People; Representation; José Artigas